Discovering Hidden Messages in Covid-19 Advertisement â€œStay Home Save Livesâ€: A Semiotic Analysis - Ni Made Desi Trisnayanti; Desak Putu Eka Pratiwi; Komang Dian Puspita Candra (RETORIKA: Jurnal Ilmu Bahasa, 2021)
COVID-19 (Coronavirus Disease 2019) is a disease caused by a new type of coronavirus. WHO officially declared COVID-19 as a global pandemic. Both government and non-government parties work together to educate people and provide information about COVID-19 through various ways. Advertisement is considered as one of the effective ways to provide education and understanding about COVID-19. This study aims to discover the hidden messages in COVID-19 advertisements by analyzing the verbal and non-verbal signs used in the advertisement entitled â€œStay Home Save Liveâ€. The data were collected by using observation method and note-taking technique. The data were analyzed by descriptive qualitative method using semiotic theory proposed by Saussure (1983) and the theory of meanings proposed by Barthes (1977). The analysis was presented by informal method. The finding shows that both verbal and visual signs in the advertisement â€œStay Home Save Livesâ€ have hidden message. Generally, it delivers a message that during this difficult time, people can defeat COVID-19 by staying at home, obeying the health protocol, and being positive.